Head morphology of 1st and 5th instar nymphs of Triatoma circummaculata and Triatoma rubrovaria (Hemiptera, Reduviidae) - da Rosa, J. A.; Barata, JMS; Cilense, M.; Neto, FMB (Elsevier B.V., 1999)
Morphological structures of the head of 1st and 5th instar nymphs of Triatoma circummaculata and Triatoma rubrovaria were revealed by analysis using scanning electron microscopy (SEM). Differences between Ist and 5th instar nymphs of these two species were observed in the postocular callosity, the number of ommatidia and tapered hair, the small segment between antennal segments, the rostrum third segment and slit lines. These slit lines were different only in the 5th instar. Similarities observed were the presence of tapered hairs in the joints, and the type of sensilla in the antennal segments. Only the Ist instar shows anteclypeus and gena sensilla. The antennal segments comprise the following types of sensilla: basiconica, bristles type I, bristles type II, bristles type III, campaniformia, coeloconica, chemosensilla, placodea, trichobothria and trichoidea. We describe here for the first time six (3+3) sensilla basiconica on the dorsal portion of the first segment of the rostrum. (C) 2000 Elsevier B.V. Ltd. All rights reserved.
Keywords: antennae; joints; sensilla; rostrum; ommatidia